Perturbed Robe's restricted problem of 2+2 bodies when the primaries form a Roche ellipsoidtriaxial system. Issue 2 (2nd July 2016) - Kaur, Bhavneet; Aggarwal, Rajiv; Yadav, Sushil
Abstract: The aim of this paper is to study the effect of perturbations in the Coriolis and centrifugal forces on the location and stability of the equilibrium solutions in the Robe's restricted problem of 2+2 bodies under the assumption that the hydrostatic equilibrium figure of the first primary is a Roche ellipsoid and the shape of the second primary is triaxial. The third and the fourth bodies (of mass m 3 and m 4 respectively) are small solid spheres of density ρ 3 and ρ 4 respectively inside the ellipsoid, with the assumption that the mass and the radius of the third and the fourth body are infinitesimal. We assume that m 2 is describing a circle around m 1 . The masses m 3 and m 4 mutually attract each other, do not influence the motion of m 1 and m 2 but are influenced by them. We have taken into consideration all the three components of the pressure field in deriving the expression for the buoyancy force viz (i) due to the own gravitational field of the fluid (ii)that originating in the attraction of m 2 (iii) that arising from the centrifugal force. The linear stability of this configuration is examined. It is observed that there exist only six equilibrium solutions of the system, provided they lie within the Roche ellipsoid. The equilibrium solutions of m 3 and m 4 lying on x 1 -axis are unstable for ε > 0, ε ′ > 0 and ε < 0, ε ′ > 0 and stable for ε > 0, ε ′ < 0 and ε < 0, ε ′ < 0, using the data of submarines in the Earth -Moon system. The equilibrium solutions of m 3 and m 4 respectively when the displacement is given in the direction of x 2 or x 3 − axis are conditionally stable.We observe that the conditions of stability are influenced by the small perturbations in the Coriolis and centrifugal forces.